1995
DOI: 10.1203/00006450-199507000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Sympathetic Activity in Children with Various Congenital Heart Diseases

Abstract: We studied the a-and P-adrenoceptor activity and catecholamine and cAMP levels in 112 children and infants admitted to the hospital for diagnostic or inte~entional catheterization of tetralogy of Fallot, ventricular septa1 defects with or without hypertension, pulmonary stenosis, coarctation of the aorta, and various complex cyanotic congenital cardiac diseases and compared them with 14 children undergoing transcatheter occlusion of patent ductus arteriosus with insignificant left-to-right-shunts. The mean tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…This is in accordance with the findings of elevated norepinephrine levels in patients with pulmonary stenosis and in patients with residual right ventricular outflow tract obstruction following surgery [27][28][29]. The limitation of cardiac output might be partially responsible [30].…”
Section: Discussionsupporting
confidence: 88%
“…This is in accordance with the findings of elevated norepinephrine levels in patients with pulmonary stenosis and in patients with residual right ventricular outflow tract obstruction following surgery [27][28][29]. The limitation of cardiac output might be partially responsible [30].…”
Section: Discussionsupporting
confidence: 88%
“…We have now shown that norepinephrineinduced relaxation is also significantly decreased in the airways. Hislop (21) found that the normal postnatal increase in ␤ adrenoceptor density was attenuated in both pulmonary arterial endothelium and bronchial epithelium in piglets exposed to hypoxia from birth for 3 d. Similarly lymphocyte ␤ adrenoceptor density was attenuated by 27% and platelet ␣ adrenoceptor density was increased in children with congenital heart disease with left-to-right shunts and pulmonary hypertension (22). This reduction of ␤ adrenoceptors in pulmonary hypertension, in addition to impaired endothelial nitric oxide release (9), may explain the reduced adrenoceptor stimulated pulmonary arterial and bronchorelaxation we observed in our study.…”
mentioning
confidence: 99%
“…The decrease in HF power was proportionally less than that of the LF power between the Control group and the PDA group, leading to a decrease in LF/HF ratio from 5.52 ± 3.28 (Control group) to 2.74 ± 1.67 (PDA group), consistent with parasympathetic dominance. In children and neonates, major reduction in HRV power has been described in intracerebral haemorrhage [9], severe sepsis [10], RDS, the aftermath of Fontan open-heart surgery [11] and pulmonary stenosis [12]. The low HRV power observed in our study in preterm infants with PDA (i.e.…”
Section: Discussionmentioning
confidence: 77%